Synthesis and Investigation of the Structural Characteristics of Zinc Oxide Nanoparticles Produced by an Atmospheric Plasma Jet - Aadim, Kadhim A.; Abbas, Ibrahim K. (Iraqi Journal of Science, 2023)
In this paper, ZnO NPs were prepared using D.C high-voltage and high frequency with an output of 6 kHz at two different preparation times preparation (10,12) minutes. Transmission electron microscopy (TEM) with (FE-SEM) was used to examine the homogenous, compact, and dense surface of the zinc oxide nanoparticles created with apparent grain size determined by (XRD), XRD results explain that the increase of the preparation time from 10 minutes to 12-minute caused an increase in crystallite size. In addition, FE-SEM showed that the increase in the ZnO NPs cluster distribution with particle size increases with increasing the preparation time. AFM was also utilized to determine the degree of cooperation between the surfaces of the zinc oxide nanoparticles, with having a high degree of stability by zeta potential -13.3±1.8mV at 12 minutes.